2013
DOI: 10.1158/1940-6207.capr-12-0426
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Chemopreventive Effect of Progestin Unrelated to Ovulation on Reproductive Tract Cancers in the Egg-laying Hen

Abstract: Epidemiologic, laboratory, and animal evidence suggests that progestins and vitamin D may be potent ovarian cancer preventives. Our objectives were to evaluate progestins as reproductive tract cancer chemopreventives in the chicken, determine whether restricted ovulation affected the incidence of reproductive tract tumors, and assess whether vitamin D would confer cancer protection either alone or in addition to progestin. A total of 2,400 two-year-old Single Comb White Leghorns were randomized into six groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, a study of sheep ovarian cancer cells indicated that progesterone is involved in the restoration or apoptosis of ovarian surface epithelial cells containing damaged DNA after ovulation . Synthetic progestin induces apoptosis in ovarian cancer cell lines, and treatment with progestin induces apoptosis in the ovarian epithelium of macaques and chickens . Furthermore, oral contraceptives with high‐progestin potency seem to provide greater protection against ovarian cancer than low‐progestin formulations .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study of sheep ovarian cancer cells indicated that progesterone is involved in the restoration or apoptosis of ovarian surface epithelial cells containing damaged DNA after ovulation . Synthetic progestin induces apoptosis in ovarian cancer cell lines, and treatment with progestin induces apoptosis in the ovarian epithelium of macaques and chickens . Furthermore, oral contraceptives with high‐progestin potency seem to provide greater protection against ovarian cancer than low‐progestin formulations .…”
Section: Discussionmentioning
confidence: 99%
“…In both, progestins were found to have a chemopreventive effect against ovarian (and oviductal) cancer (Rodriguez et al 1998, Barnes et al 2002, Trevino et al 2012. The effect was independent of ovulation (Rodriguez et al 2013) and likely due to the differential expression of TGFB in the ovarian epithelium, with a decreased expression of TGFB1 but an increased expression of TGFB2/3 isoforms. Because this expression pattern is associated with the induction of apoptosis in the OSE (Rodriguez et al 2002), it could enhance the clearance of genetically damaged ovarian epithelial cells (Rodriguez et al 2012).…”
Section: Hormones and Nfkb In Ovarian Cancermentioning
confidence: 99%
“…A potential protective effect of progestins in ovarian cancer prevention has been supported by studies of progestin‐only OCPs and limited observations that a higher dose of progestins in OCPs have a greater reduction of risk than lower‐dose pills . This observational evidence is supported by experiments in egg‐laying hens in which progestin treatment led to significantly fewer cancers of the reproductive tract . The role of hormonal therapy in the development of ovarian cancer remains unclear.…”
Section: Does Menopausal Hormone Therapy Cause Breast or Ovarian Cancer?mentioning
confidence: 99%